Teaming Up to Reduce "Sludge": Practical Guidance for Process Improvement - Kevin Van Winkle Dr.; Timothy Mottet Dr. (Academic Chairpersons Conference Proceedings, 2023)
Presenters will share and discuss best practices for faculty and administrative collaboration to reduce “sludge” (i.e. inefficiencies in university processes) as a way to increase faculty and staff morale.
Keywords: Process improvement; Academic Leadership; Faculty and Administrative Partnerships; “Sludge” reduction